Development of Dynamic Assisted Tooling Using TRIZ Approach for Dimple Structure Fabrication in Milling Process / Sharudin Hassan...[et al.] - Hassan, Sharudin; A. Ghani, Jaharah; Che Haron, Che Hasan; Md Dali, Mohd Nor Azam (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Most processes used for dimple structure fabrication nowadays have side effects on environment and human, high consumption of energy and high costs of machine set up. In order to solve these problems, Theory of Inventive Problem Solving (TRIZ) approach has been used to identify the appropriate process and technique to fabricate dimple structure on a flat surface. This method is chosen due to its advantage in terms of time saving and cost reduction for selecting the appropriate technique for fabricating dimple structure. Result analysis on TRIZ approach proved that milling process is a suitable technique to fabricate dimple structure on a flat surface. An assisted tooling is required to assist the dimple structure fabrication using a milling process. Prototype Dynamic Assisted Tooling Milling (DATM) has been successful developed to fabricate dimple structure.